A thermo-mechanical coupling model for predicting temperature and residual stress fields in selective laser melting - Tan, Pengfei (2018)
A three-dimensional thermo-mechanical coupling model has been developed to simulate a single-layer multi-track selective laser melting process using the finite element method. The model takes into account the powder melting, vaporization, solidification, cooling and shrinkage processes. The modeling results show that the component of the residual stresses is generally larger along the scanning direction than those along the other two perpendicular directions, and the von Mises stress reaches the maximum value in the last scanning track.